(untitled) (Tzintzun, Revista de Estudios Históricos, 2023)
This article exposes the problem of the public use of history by intellectuals. On the one hand, we have professionals dedicated to historical research and the results of their research; on the other, there are those who will use, reinterpret and disclose them at their discretion and convenience. Our objective is to analyze the way in which Fernando Díaz Ramírez and José Guadalupe Ramírez Álvarez, intellectuals from Querétaro of the 20th century, made public use of local history to disseminate their particular vision of the period of government of Saturnino Osornio from Querétaro in the early 1930’s.